(untitled) (Global Journal of Computer Science and Technology, 2024)
The strategy of digital twin DT implementation at the cyber-physical enterprises is proposed which is due to the need for high-quality and effective reconstruction of Ukraine The TISM and MICMAC methods are used to study the factors that influence the strategy of DT implementation to support the guaranteed functioning of a cyber-physical system 13 main factors that determine strategy success were identified and a model of strategy realization was built in the form of a six-level interaction diagram digraph The factors are classified by influence and dependence The substantiated conclusion is that the state support of DT implementation strategy the availability of design standards data protection methods legislative regulation and implementation experience by other enterprises are key factors to the success of strategy for DT implementation at the enterprise